Utilizing deliberative engagement for identifying implementation strategy priorities: lessons learned from an online deliberative forum with dental professionals - Inga Gruß; Tim Dawson; Charles D. Kaplan; Daniel J. Pihlstrom; Jeffrey L. Fellows; Deborah E. Polk (Implementation Science Communications, 2023)
Abstract Background Selecting effective implementation strategies to support guideline-concordant dental care is a complex process. We are drawing on data collected during the DISGO study to reflect on barriers we encountered in implementing a deliberative engagement process for discussing implementation strategies relevant to the evidence-based guideline targeted in this intervention. The goal is to identify factors that may influence the success of deliberative engagement as a technique to involve healthcare staff in identifying priorities for implementation strategies. Methods We drew on online chat transcripts from the deliberative engagement forums collected during the DISGO study. The chat transcripts were automatically generated for each discussion and captured the written exchanges between participants and moderators in all participating dental clinics. Chat transcripts were analyzed following a content analysis approach. Results Our findings revealed barriers to the successful implementation of deliberative engagement in the context of the DISGO study. Participants were not familiar with the materials that had been prepared for the forum and lacked familiarity with the topic of deliberation. Participants also did not share divergent viewpoints and reinforced existing ideas rather than introducing new ideas. Conclusions In order to ensure that obstacles that were encountered in this study are not repeated, it is important to carefully consider how staff can effectively be prepared for the deliberations. Participants must be familiar with the content of the guideline, and most questions about the content and evidence should be answered before the deliberative engagement sessions. If perspectives among staff on a guideline are homogenous, briefing materials should introduce perspectives that complement existing views among staff. It is also necessary to create an environment in which staff are comfortable introducing opinions that may not be held by the majority of colleagues. Trial registration This project is registered at ClinicalTrials.gov with ID NCT04682730. The trial was first registered on 12/18/2020. https://clinicaltrials.gov/ct2/show/NCT04682730 .